PENGARUH MEDIA PENYIMPANAN ENTRES KAKAO (Theobroma cacao L.) KLON BL- 50 TERHADAP KEBERHASILAN SAMBUNG SAMPING - Ghea Karilla Ulya; Nalwida Rozen; Ade Noferta (Jurnal Riset Perkebunan (JRP), 2020)
Cacao BL-50 clone is a superior cacao clone from West Sumatra. The BL-50 clones are most ideally propagated by side grafting. The objective of this study wa to determine the effect of various storage media of cacao scion BL-50 clone on the successful of side grafting. The present study was conducted in December 2018 to April 2019 at Balubuih Village, 50 Kota District and at Dharmasraya District. This research was a experiment used a Randomized Block Design (RBD) with three storage media namely banana midrib, curcuma sliced, and alcosorb mixed with sawdust which are repeated 6 times. The observation data were analyzed by the F test at 5% level significantly, if significantly different it was continued by the Duncan's New Multiple Range Test (DMNRT) at 5% level significantly. The results showed that the best scion storage media was a banana midrib which was able to increase the successful of side grafting of cacao BL-50 clones.